Silk fibroin-based scaffolds for tissue engineering - Ma, Li; Dong, Wenyuan; Lai, Enping; Wang, Jiamian (Frontiers in Bioengineering and Biotechnology, 2024)
Silk fibroin is an important natural fibrous protein with excellent prospects for tissue engineering applications. With profound studies in recent years, its potential in tissue repair has been developed. A growing body of literature has investigated various fabricating methods of silk fibroin and their application in tissue repair. The purpose of this paper is to trace the latest developments of SF-based scaffolds for tissue engineering. In this review, we first presented the primary and secondary structures of silk fibroin. The processing methods of SF scaffolds were then summarized. Lastly, we examined the contribution of new studies applying SF as scaffolds in tissue regeneration applications. Overall, this review showed the latest progress in the fabrication and utilization of silk fibroin-based scaffolds.